A wrinkle in time - L'Engle, Madeleine (L'Engle, Madeleine. Time quintet., 2017)
Meg Murry, her brother Charles, and their friend Calvin, embark on a journey through space and time, assisted by three otherworldly women, to find Meg's father, a physicist who disappeared while experimenting with time travel. Includes a foreword from the film's director, an author interview, and the author's Newberry Medal acceptance speech.